Health Service System “Food Safety Hospital” in Tertiary and Secondary Care Hospitals, Office of the Permanent Secretary, Ministry of Public Health, Thailand - นฤคนธ์ , ณปภัช (Journal of Health Science of Thailand, 2021)
The purpose of this research was to study the system on “food safety hospital” in tertiary and secondary hospitals of Ministry of Public Health wih the aims to (1) assess the situation on the system for “Food Safety Hospital”, (2) study food safety policy implementation, (3) study food safety management in hospitals, and (4) study limiting factors in the system. It was conducted during September 2017 – March 2018. The study was designed as a combined research/mixed method (simultaneous qualitative and quantitative design) by gathering, reviewing and analyzing the data for primary and secondary sources covering a whole food safety hospital program. For quantitative research, samples were 288 people (hospital directors and heads of responsible department purposively selected from 116 hospitals. Data were analyzed by descriptive statistics, and presented in term of percentage, mean, standard deviation. In quatitative research, a brainstorming meeting was conducted to evaluate “food safety hospital” program, with the participation of selected 10 experts, government administrators and persons from all sectors related to the program. Data were analyzed by content analysis relating to the food safety concept. The finding revealed that each of the tertiary and secondary hospitals of Ministry of Public Health had formed a provincial committee and stakeholder network to develop guideline and security measures on “food safety hospital”. Healthy food menu was available in 94.1% of the hospitals, 88.2% circulated advanced menu monthly, and 73.6% had made available 2 month food menu in advance. Upon inspection, 95.1% had passed the standard for food processing area and 85.8% passed the standard for food catering. Hospital administrators had increased support for the food safety hospital program. There was policy to control and set standard for the efficiency of the program. Such procedures included the examination of raw materials, quality control, and laboratory testing for food safety. Operational measures were set to manage unstandardized materials. For the Ministry of Health’s policy, food safety hospital policy was clearly formulated; and implementation support was provided. At the hospital level, the head of food safety hospital program was responsible for ensuring reliable procurement of qualified or certified food ingradients; and random checking was performed to detect and remove contaminations in the raw materials. As for the food producers, routing adjustment of food menu was performed to be in line with the availability of local seasonal supplies. The overall process was fully integrated in the food safety hospital program. This study identified 3 constraints or limitations: (1) insufficient supplies of raw food materials, (2) complicated process of food procurement, and (3) limited financial support. It was recommended that the food safety hospital program should be contunued to integrate fully at local level and the program be expanded to reach the district level. Long-term assessment should be performed to assess and improve the efficiency of the food safety hospital program.